GUARDIAN OF THE CONSTITUTION: REVIEWING THE ROLE OF THE CONSTITUTIONAL COURT - Muhammad Mutawalli Mukhlis; Ahmad Masum; Maskun Maskun; Yusuf Ibrahim Arowosaiye; Eka Merdekawati Djafar (Diponegoro Law Review, 2025)
The Constitutional Court of Indonesia is entrusted with safeguarding constitutional supremacy within Indonesia’s constitutional order, yet it does not possess the authority to review amendments to the 1945 Constitution. This institutional limitation creates a structural gap because constitutional amendments, despite their far reaching consequences, remain beyond judicial scrutiny. This study examines the constitutional feasibility of granting the Court authority to conduct procedural and substantive review of constitutional amendments. Using doctrinal legal research supported by comparative constitutional analysis, the article draws on Hans Kelsen’s theory of the hierarchy of norms and the Basic Structure Doctrine as developed in India and Germany to construct an evaluative framework suitable for the Indonesian context. The analysis demonstrates that the absence of judicial oversight over constitutional amendments weakens constitutional supremacy and increases the risk of democratic erosion through formally valid political processes. The article proposes a structured model of limited amendment review grounded in Indonesia’s constitutional identity, particularly the foundational principles embodied in Pancasila and the commitment to the rule of law. By articulating a contextually grounded doctrinal framework, this study contributes to contemporary debates on unconstitutional constitutional amendments and offers a normative pathway for strengthening constitutional guardianship in Indonesia.